2021
DOI: 10.3389/fonc.2020.600298
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Chinese Medicine Delivery by A New Family of Biodegradable Pseudo-Protein Nanoparticles for Treating Triple-Negative Breast Cancer: In Vitro and In Vivo Study

Abstract: Triple negative breast cancer (TNBC) has the worst overall survival among all breast cancer subtypes; 80% of TNBC harbors TP53 mutation. Gambogic acid (GA) is an herbal compound isolated from the dry brownish gamboge resin of Garcinia hanburyi. A new family of biodegradable polymer, the folate (FA)-conjugated arginine-based poly(ester urea urethane)s nanoparticles (FA-Arg-PEUU NP), was developed as nano-carrier for GA. Its anti-TNBC effects and the underlying mechanism of action were examined. The average diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The sections were subjected to hematoxylin and eosin (H&E) staining. For immunohistochemistry analysis of cleaved caspase-3, 20 tumor sections were incubated with anti-cleaved caspase-3 (1 : 400, cat#9664, Cell Signaling Technology), followed by incubation with HRP-conjugated secondary antibodies and 3,3′-diaminobenzidine and counterstained with hematoxylin. The slides were scanned using a digital pathology scanner (Leica BOND RX).…”
Section: Anti-tumor Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…The sections were subjected to hematoxylin and eosin (H&E) staining. For immunohistochemistry analysis of cleaved caspase-3, 20 tumor sections were incubated with anti-cleaved caspase-3 (1 : 400, cat#9664, Cell Signaling Technology), followed by incubation with HRP-conjugated secondary antibodies and 3,3′-diaminobenzidine and counterstained with hematoxylin. The slides were scanned using a digital pathology scanner (Leica BOND RX).…”
Section: Anti-tumor Efficacymentioning
confidence: 99%
“…18,19 GA has been reported as a potential candidate for the treatment of triple negative breast cancer (TNBC) with poor response rates to traditional hormone therapy or HER2-targeted therapy. 19,20 In general, GA can regulate multiple molecular targets and promote the crosstalk between different anti-tumor mechanisms, which provides a promising alternative treatment modality to the conventional therapeutic approaches for TNBC.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 The binding of baicalein to TLR4 that inhibits the HIF‐1α/VEGF signaling pathway holds a promising therapy for metastatic CRC treatment. In the further, we would use target delivery system such as nanoparticles 7 or aptamers 8 to deliver baicalein to the tumor site that can further enhance its anti‐CRC effect.…”
Section: Figurementioning
confidence: 99%
“…Gamboge is documented in traditional folk medicine records for the treatment of various diseases such as chronic dermatitis, hemorrhoids, bedsores and tapeworms (Zhang et al, 2012). During recent decades, a large number of pharmaceutical studies have focused on its antitumor activities and anti‐inflammatory activities (Kalita et al, 2021; Kwan et al, 2020; Panthong et al, 2007; Tan et al, 2017). As a natural product, gamboge is rich in caged polyprenylated xanthone components.…”
Section: Introductionmentioning
confidence: 99%
“…Gambogic acid (GA) is the most common and important member of the xanthone family, followed by other xanthones such as gambogenic acid (GNA), isogambogenic acid (IGNA) and β ‐morellic acid ( β ‐MA). In vitro and in vivo studies have reported that GA inhibits the growth of various tumors via different molecular mechanisms, including the induction of apoptosis, autophagy and cell cycle arrest, and the inhibition of invasion, metastasis and angiogenesis (Kashyap et al, 2016; Kwan et al, 2020; Suksen et al, 2021). In addition, GA also exerts anti‐inflammatory, antioxidant and antibacterial effects (Gunter et al, 2020; Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%